Cigarette smoke extract exacerbates hyperpermeability of cerebral endothelial cells after oxygen glucose deprivation and reoxygenation - Ashton Bernard (Nature Portfolio, 2019)
Abstract Cigarette smoking is a risk factor for stroke and is linked to stroke severity. Previous studies have shown that cigarette smoke extract (CSE) triggers endothelial dysfunction in vitro by initiating oxidative stress and/or an inflammatory response. In addition, cerebral endothelial dysfunction (particularly at the level of the blood-brain barrier [BBB]) contributes to stroke pathogenesis. Therefore, we hypothesized that cigarette smoking may influence stroke, at least in part, by exacerbating ischaemia-induced BBB disruption. To test this, we examined the effect of CSE on the permeability of cerebral endothelial cells exposed to oxygen glucose deprivation and reoxygenation (OGD + RO). We found that the loss of BBB integrity following ischaemic/reperfusion-like conditions was significantly worsened by CSE. Despite this being associated with increased mRNA expression of Nox catalytic subunits, reactive oxygen species (ROS) levels were however markedly lower. Furthermore, this occurred in association with elevated expression of antioxidant enzymes (SOD1, SOD2, and Gpx-1), suggesting an antioxidant defence response. Lastly, we found that CSE significantly upregulated mRNA expression of cytokines (IL-6 and TGF-β). Collectively, these results show that acute exposure to CSE worsens BBB disruption caused by OGD + RO, however, this is not linked to elevated ROS levels but may involve inflammatory mechanisms.